Neurofibrillary Pathology in the Infundibular Nucleus in Relation to Age and Abnormal Hormone Levels: Patologi Neurofibrilar pada Nukleus Infundibularis Terkait Usia dan Kadar Hormon Abnormal - Andon Hestiantoro; Dick F. Swaab (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: to determine whether the decline of testosterone during ageing would make this nucleus more vulnerable for NF changes (i.e. hyperphosphorylated-tau) in men, or that the decline of estrogens in the postmenopausal period would protect the infundibular nucleus in women. Methods: We investigated the infundibular nucleus in postmortem subjects. Brain materials obtained from 29 subjects in the Netherlands Brain Bank were further classified as control subjects and subjects with abnormal hormone conditions. Procedures consisted of tissue collection, immunochemical staining, and analysis of the staining intensity. Results then were collected and concluded using observational methods. Results: Elderly male subjects with low testosterone conditions showed more severe NF changes in the infundibular nucleus than postmenopausal women. The occurrence of NF changes in elderly subjects was generally accompanied by the presence of basket-like nerve terminals staining for ERÎ². Conclusion: The sex difference in NF changes in the infundibular nucleus in the elderly is due to hyperphosphorylated-tau induction in low testosterone and ageing condition in men, while in postmenopausal women the declining estrogen levels seem to protect against NF changes in this brain area. Keywords: ageing, estrogen, hyperphosphorylated-tau, infundibular nucleus, testosterone Abstrak Tujuan: untuk menentukan apakah penurunan level testosteron selama proses penuaan menyebabkan nukleus infundibularis menjadi lebih rentan terhadap perubahan neurofibrilar (NF) (misalnya hyperphosphorylated-tau) pada laki-laki atau apakah penurunan level estrogen selama masa pasca-menopause memiliki efek protektif terhadap nukleus infundibular pada perempuan. Metode: Peneliti memeriksa nukleus infundibular pada subjekpost-mortem. Materi berupa jaringan otak dari 29 subjek dari Netherlands Brain Bank lebih lanjut diklasifikasikan sebagai subjek kontrol dan subjek dengan kondisi hormon abnormal. Prosedur terdiri dari pengumpulan jaringan, pewarnaan dengan teknik imunohistokimia, dan analisis dari intensitas pewarnaan. Hasil yang didapat kemudian dikumpulkan dan disimpulkan sesuai dengan metode observasional. Hasil: Subjek laki-laki lanjut usia dengan testosteron rendah menunjukkan perubahan NF yang lebih buruk pada nukleus infundibular dibandingkan dengan wanita postmenopause. Kejadian perubahan NF pada subjek lanjut usia secara umum diikuti oleh munculnya pewarnaan pada ujung saraf berbentuk basket-like yang positif untuk ErÎ². Kesimpulan:Perbedaan jenis kelamin terkait perubahan NF pada nukleus infundibular pada subjek lanjut usia terjadi akibat induksi hiperfosforilasi taupada kondisi testosteron yang rendah yang dikombinasi oleh proses penuaan pada pria. Sedangkan pada perempuan pascamenopause, penurunan level estrogen menunjukkan efek protektif terhadap perubahan NF pada area otak ini. Kata kunci: estrogen, hiperfosforilasi protein tau, nukleus infundibularis, penuaan, testosteron